Banana Quality Managing System - Chandran, PavinRaj; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2021)
This research is aims to investigate the manner in which the quality of specific food can be maintained while prolonging its shelf life by studying the effects of the environment on the physical attributes of the food, which in this case is a banana. The research is done using banana which are observed for 72 hours in different temperatures. The device to determine the environmental factors was set up using an Arduino microcontroller, DHT11 Sensor, MQ3 Sensor. The sensors were connected to the microcontroller and a coding sequence has been written in order to make the circuit function successfully. For the banana that was placed in the cooler temperature was in good condition. For the second banana that was placed in a room temperature, at the end of the experiment, the fruit was inedible and in bad condition. The study finds that the cooler temperature is much more suited in preserving the quality and condition of the banana.